2014 International Conference on Science Engineering and Management Research (ICSEMR) 2014
DOI: 10.1109/icsemr.2014.7043658
|View full text |Cite
|
Sign up to set email alerts
|

A novel energy efficient voltage level shifter

Abstract: Level up and level down applications can be performed by using the novel Efficient Voltage Level Shifter (EVLS). Based on its input voltage the proposed EVLS can able to perform level up shift or level down shift. EVLS means, the circuit monitors its input voltage and performs level up shift, when its input voltage is low and level down shift when its input voltage is high. This novel level shifter consistently performs level up shift from 0.6V to 1.2V and level down shift from 1.2V to 0.6V. A new design of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…To verify the performance of the modified voltage level shifter for multiscaling, the reported EVLS has been implemented using 90 nm CMOS technology and simulated at the frequency of 5 MHz on Cadence Virtuoso tool. The simulated wave for the EVLS (Machiraju and Pushpamithra, 2014) for up and down voltage conversion is shown in Figures 9 and 10, respectively. The simulated waveforms for up conversion and down conversion of modified voltage level shifter with the similar inputs and conditions as EVLS are presented in Figures 11 and 12.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To verify the performance of the modified voltage level shifter for multiscaling, the reported EVLS has been implemented using 90 nm CMOS technology and simulated at the frequency of 5 MHz on Cadence Virtuoso tool. The simulated wave for the EVLS (Machiraju and Pushpamithra, 2014) for up and down voltage conversion is shown in Figures 9 and 10, respectively. The simulated waveforms for up conversion and down conversion of modified voltage level shifter with the similar inputs and conditions as EVLS are presented in Figures 11 and 12.…”
Section: Resultsmentioning
confidence: 99%
“…EVLS (Machiraju and Pushpamithra, 2014;da Rocha et al, 2008), as shown in Figure 7, consists of two parts: Vddl and Vddh, which is chosen depending upon the input voltage Vin that is realized by transistors Q1 and Q2 and level shifting, which is done by the remaining part of the circuit. Transistor Q1 is turned ON whenever Vin is at 1.2V and at the same time transistor Q2 is turned OFF, as a result of which Vdd sets to Vddh.…”
Section: Energy Efficient Voltage Level Shiftermentioning
confidence: 99%
See 1 more Smart Citation
“…CMOS technology is being widely used to meet the increasing demand for low power consumption and low delay operation in microelectronics circuit systems [2] [3]. Considerable reduction in chip size (<1 mm 2 ) has become possible with the advancement of CMOS technology which minimizes the manufacturing cost greatly.…”
Section: Introductionmentioning
confidence: 99%